An Effective Method for Acute Vagus Nerve Stimulation in Experimental Inflammation - Caravaca, April S.; Gallina, Alessandro L.; Tarnawski, Laura; Tracey, Kevin J.; Pavlov, Valentin A.; Levine, Yaakov A.; Olofsson, Peder S. (Frontiers in Neuroscience, 2019)
Neural reflexes regulate inflammation and electrical activation of the vagus nerve reduces inflammation in several models of inflammatory disease. These discoveries have generated an increasing interest in targeted neurostimulation as specific treatment for chronic inflammatory diseases. Data from the first clinical trials that use vagus nerve stimulation in treatment of rheumatoid arthritis and Chron´s disease suggest that there is a therapeutic potential of electrical vagus nerve stimulation in diseases characterized by excessive inflammation. Accordingly, there is an interest to further explore the molecular mechanisms and therapeutic potential of electrical vagus nerve stimulation experimentally in a range of experimental settings and available genetic mouse models of disease. Here, we describe a simple method for consistent electrical vagus nerve stimulation in the mouse.